Kantor Camat Bathin Viii: Komunikasi Organisasi & Kinerja Pegawai - Asmarita, Asmarita; Syamsir, Syamsir (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2022)
The purpose of the study was to see how organizational communication affects employee performance at the Bathin VIII District office, Sarolangun Regency. The background of the study found problems such as the lack of quality of work in the sub-district office of Bathin VIII, Sarolangun district, employee performance at the sub-district office of Bathin VIII, Sarolangun district, and employees of the Bathin VIII sub-district office in Sarolangun. sub-districts that still do not understand office communication. inability to communicate effectively The research used to investigate the data was a quantitative strategy supported by qualitative data, and this study used mixed methods, thus combining quantitative and qualitative approaches. The employees of the Bathin VIII District Office are the research population with a sample of 40 respondents. Questionnaires with a Likert scale, observations and interviews were used to collect data in this study. Simple linear regression analysis was used to analyze the data. The results of the study revealed that organizational communication variables had a significant effect on employee performance at the Bathin VIII District office, Sarolangun Regency. Organizational communication variable contributes to employee performance by 30.7%.